Body Mass Index and Knee Osteoarthritis: A Retrospective Cross-Sectional Study in Baptis Hospital, Batu City - Panji - Sananta; Wildan Faza Pratama; Dhelya - Widasmara; Eka Noviya Fuzianingsih (Universitas Wijaya Kusuma Surabaya, 2023)
Osteoarthritis is a chronic global and musculoskeletal disorder. This disease is associated with reduced articular cartilage integrity. The most commonly affected joint is the knee, followed by the hand and the hip. Knee osteoarthritis is associated with aging, obesity, articular cartilage, fatigue, trauma, and congenital joint deformities. Excess body weight is a factor that will exacerbate osteoarthritis. There are still meta-analysis studies involving cohort and case-control studies on osteoarthritis and body mass index (BMI) available, but the relationship between the two variables is still not assessed quantitatively. In addition, research on knee osteoarthritis and BMI is still limited, particularly at Baptis Hospital, where it has never been done. As a result, this study was carried out to determine the relationship between BMI and the degree of knee osteoarthritis. This retrospective cross-sectional study involved 33 patients who suffered from knee osteoarthritis. Data were collected from medical records, and the Kellgren-Lawrence system to assess the degree of knee osteoarthritis based on radiology findings. A total of 7 patients (21.2%) suffered from osteoarthritis grade 1, 10 patients (30.3%) had degree 2, 15 patients (45.5%) had degree 3, and one patient had degree 4. The Spearman correlation test showed that there was no significant relationship (p>0.05). So, it can be concluded from this study that there was no correlation between BMI and the degree of knee osteoarthritis patients at Baptis Hospital, Batu City.